2000
DOI: 10.1590/s0102-35862000000100003
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia adquirida na comunidade em pacientes tratados ambulatorialmente: aspectos epidemiológicos, clínicos e radiológicos das pneumonias atípicas e não atípicas

Abstract: Objetivo: Avaliar o percentual etiológico das pneumonias atípicas tratadas ambulatorialmente. Identificar os fatores epidemiológicos, clínicos e radiológicos que permitam diferenciar pneumonia atípica de não atípica. Métodos: Os pacientes foram submetidos a avaliação clínica, radiológica, coleta de escarro para estudo pelo método de Gram e sangue para testes sorológicos, incluindo Legionella pneumophila, Chlamydia sp, Mycoplasma pneumoniae, vírus Influenza A e Influenza B, no primeiro dia e 21 dias após inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
1
14
0
5
Order By: Relevance
“…(14,15) The percentage found in this study sample is in accordance with the variation shown in other studies. (1)(2)(3)(4)(5)(6)(16)(17)(18)(19) The infection typically affects elderly individuals with preexisting chronic pathologies such as COPD, cardiovascular diseases, alcoholism and diabetes mellitus, as well as hemodialysis patients with chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…(14,15) The percentage found in this study sample is in accordance with the variation shown in other studies. (1)(2)(3)(4)(5)(6)(16)(17)(18)(19) The infection typically affects elderly individuals with preexisting chronic pathologies such as COPD, cardiovascular diseases, alcoholism and diabetes mellitus, as well as hemodialysis patients with chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…In a study of individuals with CAP who were treated as outpatients, Rocha et al found similar results. (5) Chief among the limitations of the present study are the small sample size, the fact that the PSI criteria was not used as a variable in the decision-making process regarding hospitalization, and the fact that other criteria, such as the CURB-65 or CRB-65 scores, which could identify severe cases missed by the PSI, were not used. In addition, no standard treatment protocol was followed after the cases were diagnosed.…”
Section: Discussionmentioning
confidence: 96%
“…Little is known about the microbiological patterns at the local and regional levels or about the patterns of CAP severity in adults in Brazil. (5,6) Treatment protocols and case management protocols are often based on investigations of the disease in countries in the northern hemisphere. It should be borne in mind that the worldwide multicenter antimicrobial surveillance program, known as SENTRY, and the Latin American Sistema Regional de Vacunas (Regional Vaccination System) II program have been a reference for guiding therapy in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations